Calculation of geometrical parameters of the cossettes scalder - Zotkina, Larysa; Verhola, Georgy; Melnyk (Tkachuk), Nataliia (My University, 2013)
The process of cossettes scalding are examined. The exploration objective is the development of calculation methods for the parameters of the countercurrent cossettes scalders. The research techniques are based on physicochemical laws of constitutional changes and on industrial data processing. The basic stages of cossettes scalding are: preliminary heating of cossette, final heating of cossette, separation of blood and scalder mixture and foam, defoaming.The formulas for calculation of scalder diameter, the length of countercurrent and mixing parts, as well as the diameter of defoamer are proposed reasoning from optimum hydrodynamic conditions in a scalder.The basic dimensions for the scalders of different productivity are adduced.
Keywords: scalding; beet; foam; gas; extract; ошпарювач; буряк; піна; газ; екстракт; кафедра процесів і апаратів харчових виробництв